PENERAPAN MESIN HOT PRESS SEKAM PADI UNTUK PEMBUATAN PARTICLE BOARD PALLET DI DESA TENAJAR KEC.KERTASEMAYA- INDRAMAYU - Sifa, Agus; Badruzzaman, B; Mahfud, M; Selin, Melia; R, Rachmatullah (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2023)
Indramayu district. After harvest, many farmers burn straw and rice husks, this produces air pollution and has a detrimental impact on the environment. Rice husks can be used as particle boards and have been developed so that they can be used as an alternative material for insulators, especially for cold storage. The process of making particle board is done by molding rice husk powder through a heating and pressing process. The pressing process on a hot press machine uses a pneumatic system and the heating process uses a heater. The process of making particle board using a hot press machine is carried out using an automatic heating and pressing system. The perfect temperature and time is 175°C and 15 minutes.